(untitled) (REMUNOM, 2025)
The objective of this research aims to verify the behavior of a solid biofertilizer produced from a mixture of type “A” carnauba wax heated to its melting point followed by the addition of norbixin through physical-chemical, toxicological and application characterizations. The physicochemical characterizations carried out were DRX, FTIR, TGA, DSC. The toxicity test with Allium cepa was carried out as a biological test and the biofertilizer application test in humous soil. The results obtained revealed that there was a decrease in the crystallinity of the biofertilizer in accordance with the increase in the amount of norbixin. The absorption bands showed that norbixin contains functional groups capable of performing intermolecular interactions with the carnauba wax chain. There was no change in the thermal stability of the biofertilizer, nor was there any change in the melting temperature between the wax and the biofertilizer produced. The biofertilizer did not reveal toxicity in the proportions of norbixin added. However, when applying biofertilizer to moist soil, it is necessary to carry out longer tests, that is, longer than 10 days.